2022
DOI: 10.1017/s143192762200071x
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Complexity of Nano-Dispersoids in the Oxide Dispersion Strengthened Alloy 617

Abstract: Nanocrystalline oxides are mainly responsible for Ni-base oxide dispersion strengthened (ODS) superalloys excellent thermo-mechanical properties. To establish the microstructural correlations between the metallic matrix and various oxide dispersoids, we report here the atomic-scale structure and chemistry of the complex nano-oxide dispersoids. Ultrahigh-resolution Cs-aberration-corrected scanning transmission electron microscopy (STEM) based techniques have been used to resolve nano-dispersoids in the Alloy 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
2
0
0
Order By: Relevance
“…While the particle in Figure 7a has an incoherent interface around its periphery, the particle in Figure 7b exhibits a crystalline structure with semi-coherency with the matrix on the left side and a certain level of amorphization on the right side. A similar phenomenon which is called 'bi-phase' formation has been reported by Sinha et al in ODS IN617 alloys [43]. This has been attributed to the formation mechanisms of the Y-Al-O particles due to the reaction between Y2O3 and Al2O3 [44].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…While the particle in Figure 7a has an incoherent interface around its periphery, the particle in Figure 7b exhibits a crystalline structure with semi-coherency with the matrix on the left side and a certain level of amorphization on the right side. A similar phenomenon which is called 'bi-phase' formation has been reported by Sinha et al in ODS IN617 alloys [43]. This has been attributed to the formation mechanisms of the Y-Al-O particles due to the reaction between Y2O3 and Al2O3 [44].…”
Section: Resultssupporting
confidence: 75%
“…Figures 5e and f show an HRTEM micrograph of ~7 nm size nano-particle and corresponding FFT diffractogram, respectively. It has been found that the measured interplanar distances and angles in Table 3 are close to the parameters of hexagonal Y-Al-O (PDF# 00-054-0621) whose lattice parameters are, a = b = 0.368 nm, c = 1.052 nm, and γ = 120° [43]. However, the stoichiometry of the observed particle seems to be slightly different which is inferred from the values which are slightly off.…”
Section: Resultssupporting
confidence: 52%